CRITICAL DISCOURSE ANALYSIS IN GOD’S NOT DEAD MOVIE - Septian Mangaratua Panjaitan; Rikky Yosep Munthe; Arsen Nahum Pasaribu (Institut Pendidikan Tapanuli Selatan, 2022)
This article describes the religious reality that appears in the movie “God's Not Dead” (2014). This article is the result of research qualitative with a discourse analysis approach of the model Teun-A-Van-Dijk. Film discourse alone is not enough to rely on text, because it consists of different structures and levels. The structures are macrostructure, superstructure, and microstructure. The results of the study indicate that the preparation of the discourse is quite structured based on the thematic structure, schema, semantics, syntax, stylistics, and rhetoric. The macrostructure contains the subject structure, the super contains structure the structure schema, and the rest is contained in the microstructure. The two structural elements are true that this film lives in a very rational environment and although it does not include God in life, God still has a place in human life, indicating that there will be a message to be conveyed.